Local Community Initiative in Tackling Food Desert: Achieving Fair and Sustainable Transformation in South Memphis - Safiera Nadya Nadya Utama; Asri Saraswati (Universitas Gadjah Mada, 2022)
The issue of food desert (difficulty in accessing healthy food at affordable prices) is a phenomenon that has long plagued a number of regions in the United States. Uniquely, this issue has a close relationship with racism because the majority of the population living in food desert areas are its black population, such as the area of South Memphis, which in 2019, was nicknamed “The Hunger Capital of America”. This article aims to understand the design and implementation of solutions to the food desert issue in South Memphis using the lens of local food network and just sustainability concept. This study also aims to analyze how racial and class awareness are integrated into solutions formulated by local communities, considering that the majority of the population living in the food desert area are black and in the lower middle-class group. Related to the sustainable aspect of the just sustainability concept, this study will also evaluate how initiatives such as farmer’s markets and community kitchens in the form of non-commercial practices, can be an effective and sustainable solution to the food desert issue in the long term.